Biphasic protective effects of macrophage migration inhibitory factor in ischemia/reperfusion-induced acute kidney injury - Yiwei Du; Chunni Feng; Lu Zhou; Tingting Wang; Heng Ma; Hongbao Liu (Communications Biology)
Abstract Ferroptosis is involved in the occurrence and progression of renal ischemia/reperfusion (I/R) injury. Macrophage migration inhibitory factor (MIF) is a pleiotropic cytokine that is closely associated with kidney diseases. However, the underlying mechanisms between MIF and ferroptosis in acute kidney injury (AKI) still remain unclear. In contrast to conventional strategies, we further investigate the dynamic expression and role of MIF in both ischemic and reperfusion phases. In the present study, we establish hypoxia/reoxygenation (H/R) and I/R induced AKI models, verify ferroptosis by detecting pro-ferroptotic changes and associated indicators, and use si-RNA or Adeno-Associated virus (AAV) to knock down the expression of MIF, observing subsequent changes of ferroptosis. The results show that treatment with recombinant MIF reduces lipid ROS generation and MDA levels, upregulating glutathione (GSH) levels, with increasing AMP-activated protein kinase (AMPK) phosphorylation. While the deficiency of MIF blunted its protective effect on renal tubular epithelial cells, which demonstrates that MIF ameliorates ferroptosis injury via activating the AMPK pathway in the ischemia stage and increasing GSH content in the reperfusion stage. In conclusion, our results suggest the nephroprotective role of MIF in inhibiting ferroptosis and provide insight into the prevention and treatment of AKI.